2018
DOI: 10.1002/hbm.24438
|View full text |Cite
|
Sign up to set email alerts
|

Deviance detection is the dominant component of auditory contextual processing in the lateral superior temporal gyrus: A human ECoG study

Abstract: Auditory contextual processing has been assumed to be based on a hierarchical structure consisting of the primary auditory cortex, superior temporal gyrus (STG), and frontal lobe. Recent invasive studies on mismatch negativity (MMN) have revealed functional segregation for auditory contextual processing such as neural adaptation in the primary auditory cortex and prediction in the frontal lobe. However, the role of the STG remains unclear. We obtained induced activity in the high gamma band as mismatch respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Abnormalities are more frequently reported in the STG and MTG than in other parts of the auditory cortex in neuroimaging studies of tinnitus (Boyen et al, 2013;Chen et al, 2014;Han et al, 2018a). The temporal gyrus is critical for auditory processing that includes simple auditory stimulus processing and semantic memory (May and Tiitinen, 2010;Recasens et al, 2014), and is a connection in the hierarchical structure of the primary auditory cortex and frontal lobe (Ishishita et al, 2019). Our results revealed abnormal brain responses in this region, suggesting their involvement in tinnitus.…”
Section: Discussionmentioning
confidence: 53%
“…Abnormalities are more frequently reported in the STG and MTG than in other parts of the auditory cortex in neuroimaging studies of tinnitus (Boyen et al, 2013;Chen et al, 2014;Han et al, 2018a). The temporal gyrus is critical for auditory processing that includes simple auditory stimulus processing and semantic memory (May and Tiitinen, 2010;Recasens et al, 2014), and is a connection in the hierarchical structure of the primary auditory cortex and frontal lobe (Ishishita et al, 2019). Our results revealed abnormal brain responses in this region, suggesting their involvement in tinnitus.…”
Section: Discussionmentioning
confidence: 53%
“…In a human ECoG study, we have previously demonstrated that high gamma oscillation induced by the mismatch paradigm was widely distributed in the superior temporal gyrus, rather than within a limited area adjacent to the Sylvian fissure. Furthermore, mismatch response was shown to be attributable to deviance detection rather than adaptation (23). N1 adaptation did not account for the characteristics of the mismatch response.…”
Section: Introductionmentioning
confidence: 82%
“…MMN can also be measured with electrocorticography (ECoG), which has high spatial resolution. Investigation of ECoG with various paradigms is useful for identifying the precise location of neural circuits underlying MMN in various paradigms (52). In addition, MMN is used as a biomarker for clinical trials (53,54).…”
Section: Discussionmentioning
confidence: 99%